Mycotoxins production by Fusarium and Aspergillus species isolated from cornmeal - Mohd Zainudin, Nur Ain Izzati; Perumal, Nithiyaa (Friends Science Publishers, 2015)
Corn is a vital food source for human consumption, animal feed as well as industrial processing. However, corn faces repeated spoilage and contamination by a huge range of fungi especially by Fusarium and Aspergillus species. These fungi are known of producing mycotoxins such as fumonisins (FBs), moniliformin (MON), zearalenone (ZEA), beauvericin (BEA) and aflatoxins (AFs). The main objective of this study was to quantify the mycotoxins produced by both fungi associated with cornmeal in Malaysia. The extracted mycotoxins were qualitatively analyzed using A. salina bioassay, and quantitatively using ultra-fast Performance Liquid chromatography (uFLc). Three hundred and fourteen isolates of microfungi were obtained, 90.5% isolates belonged to Aspergillus species, namely A. flavus (76.8%), A. niger (7.6%), A. nidulans (4.5%) and A. fumigatus (1.6%). Another 9.6% isolates were Fusarium species, identified as F. verticillioides (4.5%), F. semitectum (3.2%) and F. proliferatum (1.9%). As for the mycotoxin analysis, out of 40 isolates of Aspergillus, 29 isolates produced AFB1 and only two isolates produced AFB2. Fifteen out of 16 Fusarium isolates produced MON, 12 isolates produced BEA and all isolates produced FBb but none of them produced ZEA. The analysis of A. salina revealed that all the five mycotoxins extracts were toxic to the brine shrimp despite the concentration of the mycotoxins.